Pengaruh Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan GCG Sebagai Variabel Intervening pada Perusahaan Sub Sektor Semen yang Terdaftar pada BEI Tahun 2018-2022 - Hana Damayanti Tarihoran; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to investigate the role of Good Corporate Governance (GCG) in mediating the influence of profitability and company size on company value in cement sub-sector companies listed on the Indonesia Stock Exchange, with a population involving all cement sub-sector companies listed on the Exchange. Indonesian Effect. The sample was selected using a purposive sampling technique, resulting in six companies as samples. Data analysis was carried out using mediation path analysis using Smart PLS (Partial Least Square) which involves the PLS method, including Outer Model Analysis, Inner Model Analysis, and Hypothesis Testing. The research results show that profitability has a positive and significant influence on Good Corporate Governance (GCG), while company size has a negative and significant influence on GCG. Profitability has a positive but not significant influence on company value, while company size and GCG have a positive and significant influence on company value. In addition, GCG as a mediator between profitability and company value has a positive but insignificant influence, while GCG as a mediator between company size and company value has a negative and insignificant influence.